Reflections on Contrasting Views on Themes in Chinese Civilization - Haaland, Gunnar (Dhaulagiri Journal of Sociology and Anthropology, 2011)
CORRECTION: On Page 9, Paragraph 3, Line 7, the date of the Yüan dynasty (1279 – 1368) has been changed to Yüan dynasty (1271 – 1368). Like any complex civilization, China contains the confluence of range of traditions of knowledge that people draw on in their interpretations of and reactions to events in the 'world' they are exposed to. However traditions of knowledge serve multiple purposes and may lead to contradictory views on important issues. Chairman Mao when reflecting on two dominant cultural traditions – the Confucian school and the Legalist school - stated that in China there is always two opposite viewpoints. The traditions of knowledge expressing such divergent viewpoints had for more than 2000 years been nurtured and elaborated in the organizational context of the Chinese Empire. An important concern in these traditions is their emphasis on lessons to be drawn from past historical experiences. In the present situation the historical consciousness allows for alternative guidelines for interpreting events taking place on national as well as on global arenas. Keywords: modern China; Leninist capitalism; Confucian superstructure; guanxi; corruption; mianzi (face) DOI: 10.3126/dsaj.v4i0.4510 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.1-20